Universal Design for Learning (UDL) to Facilitate the Learning of Students with Intellectual Disabilities within the Inclusive Educational Context in Sarawak, East Malaysia - Rosnani, Saini; Zaimuariffudin Shukri, Nordin; Mohd Hafizan, Hashim; Mohamad Taha, Abol (SPED sp.z o.o., 2024)
This study aims to explore the difficulties faced by Intellectual Disabilities (ID) students to learn in inclusive educational settings, and strategies incorporated by the teachers using Universal Design Learning (UDL) to facilitate effective learning of ID students. A qualitative study through document analysis and semi structured interview has been conducted. The informants are 4 special education teachers teaching at Special Education Integration Program (SEIP) classes. Findings indicate that ID students face difficulties comprehending complex concepts and require simplified instructions. Additionally, they also face difficulties in social interactions, articulation-based communication, and sensory sensitivities; exhibit behavioral or emotional challenges that affect their learning and classroom dynamics. There are also limited resources and support service to support ID students within the educational system in Sarawak, East Malaysia can be very challenging. It is necessary for the teachers to modify the different teaching methods so ID students can reach their full potential in learning. Flexibility, visual aids, technology aids, and clear voice and speech are among the strategies used by the teachers. This study can assist ID students to become more socially and functionally literate.